SISTEM INFORMASI AKADEMIK AMIK IBRAHIMY BERBASIS WEB - Ahmad Homaidi (Jurnal Ilmiah Informatika, 2016)
The rapid development of technology was felt by universities, especially the academic division in managing information as well as related to academic division, such as the study plan card and study results card. Academic information system design was considered very helpful in accelerate service process to students and lecturers. Therefore, academic information systems built using prototype methode, so that every stage can be demonstrated to campus, especially academic division, so that in manufacture process according to necessity. In this method there are several stages; Requirment Analysis, Build Prototype, Prototype Evaluation, Implementation, Testing, System Evaluation, and Use The System. By this application, students no necessary come to campus again to conduct study plan card as well as take results study card, Also like lecturers can execute to input the value with this information system that created.